Cytotoxicity, genotoxicity and cell adhesion study of Electrospun silk/surface modified nanosilica composite for Bone regeneration applications - PRINCY ALEXANDER,; PRASEETHA P.K,; PRASEETHA P.K,; S. MARIA CELESTIN VIGILA, (International Journal of Pharma and Bio Sciences, 2017)
Natural osseous tissues comprises of a nanocomposite structure which imparts structural and biological properties to it. Hence for successful and efficient regeneration of these tissues, the biomaterial used should essentially mimic the living bone tissue. Since such a biomaterial is currently unavailable, nanocomposites are promising candidates as they can provide the appropriate matrix environment as well as integrate desirable biological properties. The current paper explains an organic-inorganic nanocomposite scaffold that can be utilized for bone tissue engineering which constitutes nanosilica extracted from an agricultural waste such as rice husk and silk extracted from Bombyx Mori silkworm. One major advantage is that the material is cost-effective since the source for synthesis is natural. The scaffold is fabricated using electrospinning technique and characterized using XRD, FTIR, FESEM and TG/DTA. The in vitro study shows that this scaffold is biocompatible with L929 cells and also promotes cell adhesion with lower genotoxic activity.